ANALISIS KEMAMPUAN KONEKSI MATEMATIKA SISWA PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Duha, Agusmina (Universitas Nias Raya, 2024)
variable linear equation material for class VIII SMP Negeri 2 Teluk in the 2020/2021 academic year. This research is qualitative research that is associative in nature. To determine students' mathematical connection abilities in one-variable linear equations. The data source in this research was 18 students in class VIII of SMP Negeri 2 Telukdalam. Based on the results of the data analysis that has been presented, the researcher will present the research results based on descriptive analysis. Of all the subjects in the medium ability and low ability categories, it is stated that the indicators of using and assessing the relationship between PLSV concepts and other fields of science, students have poor mathematical connection abilities. students in the high ability category are able to solve questions well according to indicators of mathematical connection ability. Because all indicators are met, students who have high abilities also have good mathematical connection abilities. Thus, students who have high abilities will be able to use mathematical connection skills well.